al-Ilzam fi masa'il al-ahwal al-shakhsiyah : dirasah fiqhiyah muqaranah - al-Rabi', Walid Khalid ('Amman : Dar al-Nafa'is, 2007)
Domestic relations (Islamic law); comparative study
Keywords: Obligations (Islamic law); Domestic relations (Islamic law)